2021
DOI: 10.1177/17531934211056998
|View full text |Cite
|
Sign up to set email alerts
|

A protocol-based treatment plan to improve shoulder function in children with brachial plexus birth injury: a comparative study

Abstract: Children with permanent brachial plexus birth injury have a high risk of developing posterior shoulder subluxation. In 2010, we implemented a protocol to reduce the incidence of this deformity, including early passive exercises, ultrasound screening, botulinum toxin-A injections, shoulder splinting and targeted surgeries. Two-hundred and thirty-seven consecutive children treated at our institution, with a mean follow-up of 11 years (range 1 to 17) were compared in three groups: children born from 1995 to 1999 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Early emphasis is placed on shoulder position. We agree with the findings of the group from Helsinki 1 suggesting that early splinting can prevent the need for later operative intervention. Similar findings have been suggested by the group from British Columbia Children's Hospital in Vancouver (the Sup-ER—supination external rotation splint), 2 as well as Texas Scottish Rite in Dallas.…”
Section: Role Of Therapy and Shoulder Orthosessupporting
confidence: 91%
“…Early emphasis is placed on shoulder position. We agree with the findings of the group from Helsinki 1 suggesting that early splinting can prevent the need for later operative intervention. Similar findings have been suggested by the group from British Columbia Children's Hospital in Vancouver (the Sup-ER—supination external rotation splint), 2 as well as Texas Scottish Rite in Dallas.…”
Section: Role Of Therapy and Shoulder Orthosessupporting
confidence: 91%
“…45 a promising conservative therapy protocol to reduce posterior subluxation and thus the need for surgery has been made by Grahn et al 7 this study showed a reduction of the need for relocation surgery from 28% to 7% by using passive motion exercises, early ultrasound screening, BtX injections in the internal rotators, and splinting. 7 the goal of this review was to evaluate the surgical therapy options for BPBP patients, therefore studies describing the conservative therapy only were excluded. the c5-c6 lesion represents 46% to 62% of all BPBP cases, the c5-c7 lesion represents 28% to 30%, and total plexopathy (c5-c8) represents around 10% to 20%.…”
Section: Discussionmentioning
confidence: 95%
“…The effectiveness of conservative therapy, including physiotherapy, botulin toxin A (BTX) injections, thermoplastic braces, and kinesiology taping is still debated for preventing contractures, muscle shrinkage, and joint deformities. 45 A promising conservative therapy protocol to reduce posterior subluxation and thus the need for surgery has been made by Grahn et al 7 This study showed a reduction of the need for relocation surgery from 28% to 7% by using passive motion exercises, early ultrasound screening, BTX injections in the internal rotators, and splinting. 7 The goal of this review was to evaluate the surgical therapy options for BPBP patients, therefore studies describing the conservative therapy only were excluded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations